Relative Price Variability, Real Shocks, and the Stock Market - KAUL, GAUTAM; SEYHUN, H. NEJAT (Journal of Finance, 1990)
ABSTRACT In this paper, we investigate the effects of relative price variability on output and the stock market and gauge the extent to which inflation proxies for relative price variability in stock return‐inflation regressions. The evidence shows that the negative stock return‐inflation relations proxy for the adverse effects of relative price variability on economic activity, particularly during the seventies, when the U.S. experienced oil supply shocks. Hence, it appears that inflation spuriously affects the stock market in two ways: the aggregate output link of Fama (1981) and the supply shocks reflected in relative price variability.